Deaf and Hard of Hearing Early Intervention: Perceptions of Family-Centered Practice. (September 2021) - Stewart, Victoria; Slattery, Maddy; McKee, Jen
This cross-sectional quantitative study investigated parents' perceptions of the quality of family-centered practice in an early intervention service for young children who are deaf or hard of hearing through the use of the Measures of Processes of Care (MPOC-56). The results indicated that the majority of families accessing the service were satisfied with the family-centered practices they were receiving. Consistent with previous studies in different disability settings, families were least satisfied with the provision of general information regarding the child's disability, identifying further access to unbiased information and resources is needed. This highlighted a tension in the role of organizations operating within individualized funding models in regard to who is responsible for the dissemination of reliable and evidence-based general information. As the MPOC-56 has not been used in deaf or hard of hearing populations previously, this study found it was an appropriate measure for caregiver perceptions of family-centered practice within this population.